Role of hysterolaparoscopy in unexplained infertility - Choudhary, Shubha; V., Meena Priyadharshini; Sirsat, Ameya; Tandulwadkar, Sunita R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Infertility, as defined by World Health Organization (WHO), is failure to achieve pregnancy during 1 year of regular unprotected intercourse. The objective of this study was to determine the incidence of unsuspected pathology at hysterolaparoscopy in presumed unexplained infertility, the incidence of intervention done for correcting pathology and its outcome and the importance of hysterolaparoscopy in the evaluation and treatment of infertile couples. Methods: This prospective observational study was carried out at IVF and Endoscopy centre, Department of obstetrics and gynecology at the Ruby Hall clinic, Pune from 1st November 2014 to 30th July 2016, after obtaining institutional ethical clearance and who met the inclusion and exclusion criteria. A detailed clinical history and physical examination and bimanual pelvic examination were done, following which all the patients were subjected to baseline blood investigation, 3D pelvis (TVS) and semen analysis. Day care hysterolaparoscopy was performed and systematic analysis were done. Results: The mean duration of infertility was 2 to 4 years. In our study out of 75 women 62 (82.67%) showed normal hysteroscopic findings, remaining 13 women (17.67%) showed abnormal hysteroscopic findings like cornaul blockage, intrauterine adhesions and tuberculosis endometrium. Abnormal laparoscopic findings were reported in 29.33% of which the most common pathology was endomertiosis (21.33%). Conclusions: Diagnostic Hysterolaproscopy is a safe, effective, minimally invasive, cost effective, daycare comprehensive procedure in evaluation of unexplained infertility. Apart from routine diagnostic protocol missed pathologies can be detected and this tool can be used for diagnostic as well as therapeutic intervention.